2013
DOI: 10.2320/matertrans.mi201208
|View full text |Cite
|
Sign up to set email alerts
|

Non-Basal Slip Systems Operative in Mg<sub>12</sub>ZnY Long-Period Stacking Ordered (LPSO) Phase with 18R and 14H Structures

Abstract: Non-basal slip systems in the Mg 12 ZnY long-period stacking ordered (LPSO) phase, the operational frequency of which is increased at high-temperatures and affects the mechanical properties, were clarified. The f1 100gh11 20i prism slip was identified in both 18R and 14H LPSO phases, even though they have the different lattice systems. This behavior is different from that observed in a Ni-based LPSO phase. The peculiar chemical modulation in the Mg 12 ZnY LPSO phase may affect the selection of operative slip s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 29 publications
(36 reference statements)
2
14
0
Order By: Relevance
“…While it was recently reported that in the Mg-based LPSO phase DS crystal only basal slip system was predominantly activated compared to the other slip systems in deformation at room temperature. 26,27) Because of this fact, contributions from non-basal slips and twinning to kinking should be limited in the case of this alloy system. Figures 1(f ) and (g) shows an optical micrograph of the surface morphology and the crystal orientation map in the deformed LPSO phase DS crystal.…”
Section: Overview Of the Intragranular Misorientations Duementioning
confidence: 99%
“…While it was recently reported that in the Mg-based LPSO phase DS crystal only basal slip system was predominantly activated compared to the other slip systems in deformation at room temperature. 26,27) Because of this fact, contributions from non-basal slips and twinning to kinking should be limited in the case of this alloy system. Figures 1(f ) and (g) shows an optical micrograph of the surface morphology and the crystal orientation map in the deformed LPSO phase DS crystal.…”
Section: Overview Of the Intragranular Misorientations Duementioning
confidence: 99%
“…The plate-shaped LPSO phase and/or solute-segregated SF that precipitates coherently in the a-Mg matrix promotes h1 0 1 0i//ED fiber texture evolution. Hagihara et al [56,57] demonstrated that the dominantly operative slip systems of the 18R-and 14H-LPSO phases in an Mg alloy were (0 0 0 1)h1 1 2 0i slip at all temperatures and {1 0 1 0}h1 1 2 0i slip at elevated temperatures >673 K. Strong plastic anisotropy and deformation inhomogeneity were seen at room or elevated temperature, whichever it was. Furthermore, a highly dispersive plate-shaped LPSO phase in the a-Mg matrix phase might suppress the non-basal slip in the a-Mg matrix grain.…”
Section: Effect Of Fiber Texture On Creep Propertiesmentioning
confidence: 93%
“…Factors such as precipitation kinetics and second phase evolution during heat treatments [6][7][8][9][10][13][14][15][16], and changes of microstructure and texture during thermomechanical processing [17][18][19][20][21] are receiving most attention. Other studies are examining deformation mechanisms within the matrix and second phases [12,[21][22][23][24] to understand how strengthening is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined plastic deformation at high temperatures [5,8,[21][22][23][24][25], where such alloys may find application, and one reported characteristic is the onset of flow stress serrations when straining at intermediate temperatures [26][27][28][29]. This phenomenon is known as the Portevin-Le Chàtelier (PLC) effect [30][31][32][33][34] and is a consequence of a negative strain rate sensitivity, generally brought about by dynamic strain ageing (a temporary locking of dislocations by solute accretion).…”
Section: Introductionmentioning
confidence: 99%